A half cut design of low profile UWB planar antenna for DCS/PCS/WLAN applications. Issue 9 (7th May 2019) - Tiwari, Rakesh N.; Singh, Prabhakar; Kanaujia, Binod K.
Abstract: A miniaturized half cut coalesced kite shaped printed antenna is presented for the ultrawide band (UWB) characteristics. The proposed design bears a compact and small physical dimension of 25 (L) × 9 (W) × 1.6 (h) mm 3 . This structure produces higher impedance bandwidth as compared to the corresponding full structure of the antenna design. The variation of ground plane dimension is studied to get the optimized results of the antenna. The measured impedance bandwidth (return loss <10 dB) of the proposed antenna is found to be 16.12 GHz in the frequency range 1.02 to 17.14 GHz. The average measured gain for this design is 3.12 dBi for the entire band of operation. The far field radiation patterns are also presented at 1.18, 3.1, 6.85, and 10.6 GHz. The antenna performances are first analyzed by the CST Microwave Studio, the simulation software based on finite integration technology (FIT) and then the optimized structure is fabricated for the measurements. The proposed design structure reveals the recent state of art by using the half cut technique which not only miniaturizes the size but also covers the whole UWB range to be used for many wireless systems.